Причини та види іншомовної тривожності під час вивчення другої мови - Горбач, Н. В.; Horbach , N. V.; Кальченко, Т. М.; Kalchenko, T. M.; Бортник, Ю. М.; Bortnyk , Yu. M.; Cавченко, О. О.; Savchenko, O. O.; Юлія Бортнік; Тетяна Кальченко (Наукові інновації та передові технології. - 2023. - № 14(28). - С. 945-953, 2023)
Виявлено причини іншомовної тривожності у студентів та розкрито способи її подолання. Встановлено найпоширеніші види діяльності, які викликають іншомовну тривожність серед студентів. Розглянуто подолання почуття тривожності під час вивчення другої мови та взаємозв'язок між тривожністю та іншими мовними навичками: читанням, аудіюванням і письмом.

Foreign language anxiety, also known as xenoglossophobia, is a feeling of uneasiness, apprehension, nervousness, and fear that arises when learning or using a second or foreign language. The research has shown that foreign language anxiety is a significant problem more often among adults than among children, especially in terms of its close connection with foreign language speaking skills. Motivation of university students to learn foreign languages remains important for domestic and foreign scholars. The peculiarity of this problem lies in the fact that it involves both individual characteristics and the emotional sphere of a person. Among the most common problems are the fear of communicating in a foreign language, the fear of looking ridiculous because of mistakes in speech, and the fear of forgetting the right words during a conversation. Scientists attribute this fear to the personality of the student, the teacher, and the conditions and organization of the learning process. The aim of the article is to identify the causes of students' foreign language anxiety and to indicate the ways to overcome it, to identify the most common activities that cause foreign language anxiety among students. The reduction of students' anxiety during spontaneous speech activities in a foreign language is analyzed. If the class includes one spontaneous speaking activity, the feeling of anxiety goes down sharply. It can be a game or a debate. Listening is one of the most powerful triggers of anxiety and it interferes with information retrieval. Scientists have found that there are several main sources of listening anxiety: lack of confidence; lack of listening strategies that teachers should teach; peculiarities of listening comprehension; characteristics of listening materials. Anxiety is an effective filter that causes learners with higher levels of anxiety to block comprehension, and this causes them to perform really poorly. overcome anxiety while learning a second language. The article also discusses overcoming anxiety while learning a second language and the relationship between anxiety and other language skills: reading, listening, and writing.

Выявлены причины иноязычной тревожности у студентов и раскрыты способы ее преодоления. Установлены самые распространенные виды деятельности, вызывающие иноязычную тревожность среди студентов. Рассмотрено преодоление чувства тревожности при изучении второго языка и взаимосвязи между тревожностью и другими языковыми навыками: чтением, аудированием и письмом.
Causes and types of foreign language anxiety when learning a second language
Keywords: вивчення іноземної мови; learning a foreign language; изучение иностранного языка; іншомовна тривожність; foreign language anxiety; иноязычная тревожность; побоювання; fear; опасение; нервозність; nervousness; нервозность; мовленнєва активність; speech activity; речевая активность